Writing the lost generation: expatriate autobiography and American modernism - Monk, Craig (My University, 2008)
Members of the Lost Generation, American writers and artists who lived in Paris during the 1920s, continue to occupy an important place in our literary history. Rebelling against increased commercialism and the ebb of cosmopolitan society in early twentieth-century America, they rejected the culture of what Ernest Hemingway called a place of “broad lawns and narrow minds.” Much of what we know about these iconic literary figures comes from their own published letters and essays, revealing how adroitly they developed their own reputations by controlling the reception of their work. Surprisingly the literary world has paid less attention to their autobiographies. In Writing the Lost Generation, Craig Monk unlocks a series of neglected texts while reinvigorating our reading of more familiar ones. Well-known autobiographies by Malcolm Cowley, Ernest Hemingway, and Gertrude Stein are joined here by works from a variety of lesser-known—but still important—expatriate American writers, including Sylvia Beach, Alfred Kreymborg, Samuel Putnam, and Harold Stearns. By bringing together the self-reflective works of the Lost Generation and probing the ways the writers portrayed themselves, Monk provides an exciting and comprehensive overview of modernist expatriates from the United States.